Haunted historiographies : the rhetoric of ideology in postcolonial Irish fiction - Schultz, Matthew (Professor of English) (Manchester University Press, 2014)
The rhetoric of ideology haunts Irish fiction. Schultz maps these rhetorical hauntings across a wide range of postcolonial Irish novels, and defines the spectre as a non-present presence that simultaneously symbolizes and analyzes an overlapping of Irish myth and Irish history. By exploring this exchange between literary discourse and historical events, 'Haunted Historiographies' provides literary historians and cultural critics with a theory of the spectre that exposes the various complex ways in which novelists remember, represent, and reinvent historical narrative.